THE IMPACT OF CORPORATE CULTURE ON A MANAGER’S CAREER DEVELOPMENT (Ustozlar uchun, 2025)
Corporate culture plays a decisive role in shaping a manager’s career development, influencing leadership style, motivation, communication patterns, and opportunities for advancement. This paper explores the relationship between organizational culture and managerial growth, demonstrating how values, norms, and workplace behavior shape a manager’s trajectory. The study also highlights how strong cultures foster innovation, adaptability, and long-term professional success.